2006
DOI: 10.1287/opre.1060.0327
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Supply Chain Management at the U.S. Coast Guard Using Part-Age Dependent Supply Replenishment Policies

Abstract: The United States Coast Guard (USCG), now part of the Department of Homeland Security, has the mission to secure the U.S. coastline using a combination of air and sea capabilities. This paper focuses on an application of operations research techniques at the USCG to improve the performance of its aircraft service parts supply chain. We focused on evaluating the supply chain benefits from linking the aircraft maintenance database with the aircraft parts inventory database. This required us to (a) develop an app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…This is especially relevant if preventive replacements are undesired because of the loss of a significant part of the useful lifetime of components, or if preventive replacements are (almost) equally expensive as corrective replacements (e.g., in process manufacturing, operating 24/7). The two papers that are most closely related are by Deshpande et al (2006) and Louit et al (2011); for the differences with those and other studies, see Section 2. Second, we show that large savings can be obtained via condition based spare parts supply, and we identify under which circumstances the savings are largest.…”
Section: We Model This Problem As a Discrete-time Markov Decision Promentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially relevant if preventive replacements are undesired because of the loss of a significant part of the useful lifetime of components, or if preventive replacements are (almost) equally expensive as corrective replacements (e.g., in process manufacturing, operating 24/7). The two papers that are most closely related are by Deshpande et al (2006) and Louit et al (2011); for the differences with those and other studies, see Section 2. Second, we show that large savings can be obtained via condition based spare parts supply, and we identify under which circumstances the savings are largest.…”
Section: We Model This Problem As a Discrete-time Markov Decision Promentioning
confidence: 99%
“…A related paper is that of Deshpande et al (2006) in which part-age information is explicitly used in the inventory control policy. The authors assume that a part-age signal can be observed each period, which is then compared with a certain treshold value.…”
Section: Related Literaturementioning
confidence: 99%
“…Similarly, Louit et al [82] present a model directed to the determination of the ordering decision for a spare part when the component in operation is subject to a condition monitoring program. Other related works incorporating condition monitoring information into spare parts inventory decisions can be found in [83,84,85,86].…”
Section: State-of-the-artmentioning
confidence: 99%
“…We are aware of the following papers that consider, in the context of spare parts inventory control, ADI that results from monitoring the degradation state of components in the installed base, all of which consider a periodic review model: Deshpande et al (2006), Li andRyan (2011), Louit et al (2011), and Lin et al (2012). In addition to adapting the spare parts supply, the maintenance policy may also be adapted, see, e.g., Elwany and Gebraeel (2008), Wang et al (2008), and Rausch and Liao (2010.…”
Section: Advance Demand Informationmentioning
confidence: 99%
“…However, spare parts stocks may tie up a lot of capital. Commercial airlines are estimated to have over $40 billion worth of spare parts (Harrington, 2007, p.78), a single company such as ASML, which builds lithography equipment used in semiconductor manufacturing, owns spare parts worth tens of millions of euros (Kranenburg, 2006, p.78), and the US Coast Guard Aircraft owns inventories worth over $700 million (Deshpande et al, 2006(Deshpande et al, , p.1028. Stocking the right number of spare parts, not too few and not too many, is thus of key importance.…”
Section: Introductionmentioning
confidence: 99%